A flexible fluorescent temperature sensor and a preparation method and application thereof
Patent Information
- Application Number
- CN202611292900.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]为解决传统柔性传感器在海上作业抗腐蚀能力弱的问题,本发明提供一种适用于海上作业的柔性荧光温度传感器,通过引入SiO2纳米填料对PDMS基体进行增强改性,研究表明,引入二氧化硅(SiO2)纳米填料可有效增强聚合物基体的力学性能和抗腐蚀能力,抑制环境因素对材料结构及分散状态的破坏
[0032] This invention presents a corrosion-resistant flexible fluorescence temperature sensor based on UCNPs-PDMS-SiO2 composite optical fiber. By introducing SiO2 nanofiller to enhance and modify the PDMS matrix, the sensor's mechanical strength and salt spray corrosion resistance are significantly improved while maintaining the original fluorescence temperature response sensitivity. This effectively suppresses the damage to the PDMS matrix and the dispersion state of UCNPs caused by humid heat and salt spray environments. Experiments show that in a 5% NaCl salt spray corrosion test, the fluorescence intensity-temperature response slope of the sensor without SiO2 decreased significantly from 770 to 537, while the slope of the UCNPs-PDMS-SiO2 composite sensor of this invention only changed slightly from 705 to 675, fully demonstrating the key role of SiO2 in improving salt spray corrosion resistance. Furthermore, based on the Er³⁺ ion thermal coupling energy level FIR temperature measurement mechanism, this sensor achieves accurate temperature measurement within the range of 40-130°C, exhibiting good photothermal stability and reversibility, and showing no significant hysteresis or drift during multiple heating and cooling cycles.
Smart Images

Figure CN122921391A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fiber optic sensing technology, specifically to a flexible fluorescent temperature sensor, its fabrication method, and its applications. Background Technology
[0002] Upconversion nanoparticles (UCNPs) are a class of rare-earth-doped nanomaterials that can be excited by near-infrared light and emit visible light. They possess significant advantages such as strong photostability, no background fluorescence, resistance to photobleaching, and deep tissue penetration, playing an important role in biomedicine, display technology, and optical sensing. In recent years, the application of UCNPs in temperature sensing has received widespread attention, especially fluorescence intensity ratio (FIR) temperature measurement technology based on rare-earth ion thermally coupled energy levels. Because it is unaffected by factors such as excitation light power fluctuations and probe concentration changes, it has advantages such as high accuracy, high stability, and non-contact measurement, making it an ideal temperature detection method.
[0003] However, traditional UCNPs temperature sensors mostly use rigid substrates, making it difficult to achieve flexible attachment and in-situ monitoring of complex curved surfaces (such as the ends of dry-type transformer windings and core bends). Meanwhile, in harsh operating conditions such as offshore oil and gas platforms and high-voltage power transmission and transformation facilities, power equipment is exposed to humid, hot, salt spray, and strong electromagnetic interference environments for extended periods, placing higher demands on the sensors' corrosion resistance, insulation safety, and electromagnetic compatibility. Existing electrical temperature sensors (such as thermocouples and Pt100) have inherent limitations, including high insulation risk of metal probes, poor flexibility, and susceptibility to electromagnetic interference, making it difficult to meet these application requirements.
[0004] Polydimethylsiloxane (PDMS), as a flexible optical material, possesses excellent optical transparency, chemical stability, and mechanical flexibility, making it an ideal matrix material for fabricating flexible fiber optic sensors. However, PDMS is prone to swelling and microcrack propagation in long-term humid, hot, and salt spray environments, leading to degradation of sensor performance.
[0005] In summary, there is an urgent need to develop a new type of temperature sensor that combines flexibility, corrosion resistance, and full optical properties, which can be attached to the critical curved surfaces of power equipment such as dry-type transformers to achieve in-situ, continuous, and high-precision temperature monitoring under harsh operating conditions, thereby overcoming the shortcomings of traditional electrical sensors in terms of insulation safety, spatial adaptability, and environmental tolerance. Summary of the Invention
[0006] To address the issue of weak corrosion resistance in traditional flexible sensors used in marine operations, this invention provides a flexible fluorescent temperature sensor suitable for such applications. By introducing SiO2 nanofillers to enhance the PDMS matrix, research shows that the introduction of SiO2 nanofillers effectively improves the mechanical properties and corrosion resistance of the polymer matrix, suppressing environmental damage to the material structure and dispersion. Through near-infrared laser excitation of rare-earth ion thermal coupling energy levels, and based on a fluorescence intensity ratio (FIR) temperature measurement mechanism, accurate temperature measurement over a wide temperature range is achieved. This sensor exhibits excellent flexibility and reversibility, allowing it to be attached to critical curved surfaces such as the ends of dry-type transformer windings, core bends, and clamp surfaces, enabling in-situ, continuous, and electromagnetically interference-resistant temperature monitoring.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] The first aspect of this invention provides a flexible fluorescent temperature sensor, the structure of which includes:
[0009] Plastic optical fiber core, and upconversion cladding layer covering the surface of the plastic optical fiber core;
[0010] The upconversion coating is formed by thermosetting upconversion nanoparticles, polydimethylsiloxane, silica, and a curing agent.
[0011] Preferably, the mass of the upconversion nanoparticles is 0.5-2 wt% of the mass of the polydimethylsiloxane.
[0012] Preferably, the mass of the silica is 0.5-5 wt% of the mass of the polydimethylsiloxane.
[0013] Preferably, the average particle size of the silica is 20-50 nm.
[0014] Preferably, the upconversion nanoparticles have a three-layer core-shell structure, consisting of a Gd:Er core layer, a Y:Yb intermediate shell layer, and an outermost Y shell layer from the inside out. The upconversion nanoparticles possess thermally coupled energy levels, emit visible fluorescence under near-infrared light excitation, and achieve temperature measurement based on the fluorescence intensity ratio (FIR) mechanism. The thermally coupled energy level of the upconversion nanoparticles is the ²H of Er³⁺ ions. 11 / 2 energy level and 4 S3 / 2 energy level.
[0015] Preferably, the method for preparing the upconversion nanoparticles includes the following steps:
[0016] (1) Preparation of core layer Gd:Er: Take Gd precursor and Er precursor, add oleic acid, 1-octadecene and methanol to obtain core layer precursor solution, heat to remove solvent methanol, add NH4F and NaOH, heat the mixture to 290-310°C, react for 1-2 hours to obtain Gd:Er core nanoparticles;
[0017] (2) Coating of the intermediate shell of Y:Yb: Take Y precursor and Yb precursor, add oleic acid, 1-octadecene and methanol to obtain intermediate shell precursor solution, add Gd:Er core nanoparticles synthesized in step (1), heat to remove solvent methanol, add NH4F and NaOH, heat the mixture to 290-310°C, react for 1-2 hours to form Gd:Er@Y:Yb core shell nanoparticles;
[0018] (3) Coating of the outermost Y shell: Take the Y precursor, add oleic acid, 1-octadecene and methanol to obtain an outer precursor solution, add the Gd:Er@Y:Yb core-shell nanoparticles synthesized in step (2), heat to remove the solvent methanol, add NH4F and NaOH, heat the mixture to 290-310°C, react for 1-2 hours to obtain Gd:Er@Y:Yb@Y three-layer core-shell structured nanomaterial.
[0019] Preferably, the mass ratio of polydimethylsiloxane to curing agent is (8-10):1.
[0020] Preferably, the core material of the plastic optical fiber is selected from at least one of polymethyl methacrylate, polycarbonate, cyclic olefin copolymer, and fluoroplastics; more preferably, the core material of the plastic optical fiber is polymethyl methacrylate. In some specific embodiments of the present invention, a plastic optical fiber with a core material of polymethyl methacrylate and a cladding material of fluororesin is used. When preparing the flexible fluorescent temperature sensor of the present invention, it is necessary to remove the fluororesin cladding material, which can be done by chemical stripping.
[0021] The temperature measurement range of the flexible fluorescent temperature sensor of the present invention is 40-140°C.
[0022] The near-infrared excitation wavelength of the flexible fluorescent temperature sensor of the present invention is 980 nm.
[0023] The flexible fluorescent temperature sensor of the present invention is externally connected to a 980 nm laser excitation source and a spectrometer. The excitation source continuously irradiates the flexible fluorescent temperature sensor with irradiation light, and the spectrometer is used to record the fluorescence spectrum emitted by the flexible fluorescent temperature sensor.
[0024] A second aspect of this invention provides a method for fabricating the aforementioned flexible fluorescent temperature sensor, comprising the following steps:
[0025] Upconversion nanoparticles, silica, polydimethylsiloxane, and curing agent were mixed in proportion, stirred, and degassed to obtain a UCNPs-PDMS-SiO2 composite precursor. The cladding-removed plastic optical fiber core was immersed in the UCNPs-PDMS-SiO2 composite precursor for impregnation, pull coating, and then thermal curing to obtain the flexible fluorescent temperature sensor.
[0026] In a specific embodiment of the present invention, when preparing a flexible fluorescent temperature sensor, the upconversion nanoparticles need to be pre-dispersed in a solvent to form a dispersion. Specifically, the solvent can be n-hexane.
[0027] In a specific embodiment of the present invention, when preparing a flexible fluorescent temperature sensor, the silica needs to be pre-dispersed in a solvent to form a dispersion. Specifically, the solvent can be anhydrous ethanol.
[0028] Preferably, the thermosetting temperature is 70-90°C and the time is 1.5-3 hours.
[0029] Preferably, the lifting speed is 1-3 mm / s.
[0030] A third aspect of this invention provides the application of the aforementioned flexible fluorescent temperature sensor in temperature monitoring of offshore dry-type transformers. The flexible fluorescent temperature sensor is attached to the winding ends or curved surfaces of the core bends of the dry-type transformer, enabling in-situ, continuous temperature monitoring under salt spray, humid heat, and strong electromagnetic interference environments.
[0031] Compared with the prior art, the beneficial effects of the present invention are:
[0032] This invention presents a corrosion-resistant flexible fluorescence temperature sensor based on UCNPs-PDMS-SiO2 composite optical fiber. By introducing SiO2 nanofiller to enhance and modify the PDMS matrix, the sensor's mechanical strength and salt spray corrosion resistance are significantly improved while maintaining the original fluorescence temperature response sensitivity. This effectively suppresses the damage to the PDMS matrix and the dispersion state of UCNPs caused by humid heat and salt spray environments. Experiments show that in a 5% NaCl salt spray corrosion test, the fluorescence intensity-temperature response slope of the sensor without SiO2 decreased significantly from 770 to 537, while the slope of the UCNPs-PDMS-SiO2 composite sensor of this invention only changed slightly from 705 to 675, fully demonstrating the key role of SiO2 in improving salt spray corrosion resistance. Furthermore, based on the Er³⁺ ion thermal coupling energy level FIR temperature measurement mechanism, this sensor achieves accurate temperature measurement within the range of 40-130°C, exhibiting good photothermal stability and reversibility, and showing no significant hysteresis or drift during multiple heating and cooling cycles.
[0033] The sensor of this invention possesses excellent flexibility and all-optical characteristics, enabling it to be attached to critical curved surfaces such as the winding ends, core bends, and clamp surfaces of dry-type transformers. It maintains signal stability even under strong electromagnetic interference, achieving in-situ, continuous, and high-precision temperature monitoring. It overcomes the shortcomings of traditional electrical sensors in terms of high-voltage insulation safety, spatial adaptability, and resistance to marine corrosion, providing a flexible, all-optical, and highly reliable novel sensing solution for thermal condition monitoring of offshore dry-type transformers and other power equipment. Attached Figure Description
[0034] Figure 1 The fabrication process of a flexible fluorescent temperature sensor based on UCNPs-PDMS-SiO2 composite optical fiber is shown.
[0035] Figure 2 (a) shows the appearance morphology of the UCNPs-PDMS-SiO2 flexible fluorescent sensor;
[0036] Figure 2 (b) shows the morphology of the UCNPs-PDMS-SiO2 flexible fluorescent sensor after being excited at 980 nm;
[0037] Figure 3 (a) shows the temperature and light intensity curves of UCNPs-PDMS-SiO2 before immersion in NaCl in Example 1;
[0038] Figure 3 (b) shows the FIR fitting curve of UCNPs-PDMS-SiO2 before soaking in NaCl in Example 1;
[0039] Figure 4 (a) shows the temperature and light intensity curves of UCNPs-PDMS-SiO2 after being soaked in NaCl in Example 2;
[0040] Figure 4 (b) shows the FIR fitting curves of UCNPs-PDMS-SiO2 after soaking in NaCl in Example 2;
[0041] Figure 5 (a) shows the temperature and light intensity curves of UCNPs-PDM before immersion in NaCl in Comparative Example 1;
[0042] Figure 5 (b) shows the FIR fitting curve of UCNPs-PDMS before soaking in NaCl in Comparative Example 1;
[0043] Figure 6 (a) shows the temperature and light intensity curves of UCNPs-PDMS after being soaked in NaCl in Comparative Example 2;
[0044] Figure 6 (b) shows the FIR fitting curves of UCNPs-PDMS after soaking in NaCl in Comparative Example 2. Detailed Implementation
[0045] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0046] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0047] The upconversion nanoparticles (UCNPs) used in the following examples were prepared by a method including the following steps:
[0048] (1) Preparation of Gd:Er core layer: GdCl3·6H2O (0.475 mmol) and ErCl3·6H2O (0.025 mmol) were mixed, and oleic acid (8 mL), 1-octadecene (16 mL) and methanol (10 mL) were added, followed by stirring for 5 minutes. The mixture was heated to 160°C under a nitrogen atmosphere and held for 30 minutes to remove methanol. After the solution cooled, a methanol solution containing NH4F (4 mmol) and NaOH (1 mmol) was added, and the mixture was stirred at 70°C for 1 hour to evaporate methanol. Subsequently, the mixture was heated to 300°C and reacted under nitrogen protection for 1.5 hours to obtain oleic acid-coated Gd:Er core nanoparticles (OA-core). The product was washed by centrifugation with a mixture of ethanol and ultrapure water (1:1, v / v) and then dispersed in cyclohexane for later use.
[0049] (2) Coating of the Y:Yb intermediate shell: YCl3·6H2O (0.30 mmol) and YbCl3·6H2O (0.20 mmol) were dissolved in oleic acid (4 mL), 1-octadecene (8 mL), and methanol (5 mL) as shell precursors. The synthesized OA-core was redispersed in a mixed solvent of oleic acid (4 mL) and 1-octadecene (8 mL), and heated to 120°C under nitrogen to remove cyclohexane. Subsequently, the shell precursor was added dropwise to the reaction system, and the temperature was raised to 160°C and maintained for 30 minutes to remove methanol. A methanol solution containing NH4F (2 mmol) and NaOH (0.5 mmol) was added, and after stirring for 1 hour, the reaction system was heated to 300°C and maintained for 1 hour to form the Gd:Er@Y:Yb core-shell structure. The product was centrifuged and washed, and then dispersed in cyclohexane.
[0050] (3) Coating of the outermost Y-shell. YCl3·6H2O (0.50 mmol) was dissolved in oleic acid (2 mL), 1-octadecene (4 mL), and methanol (5 mL) as the outer layer precursor. In the Gd:Er@Y:Yb core-shell nanoparticle dispersion, the above steps of heating to remove solvent, injecting precursor, adding ammonium fluoride and sodium hydroxide, and high-temperature crystallization were repeated to finally obtain Gd:Er@Y:Yb@Y three-layer core-shell structured nanomaterials. The synthesized product was centrifuged and washed three times with a mixture of ethanol and ultrapure water (1:1, v / v), and finally dispersed in cyclohexane for storage, or vacuum dried at 60°C for subsequent functionalization.
[0051] Example 1
[0052] A corrosion-resistant flexible fluorescent temperature sensor based on UCNPs-PDMS-SiO2 composite optical fiber (with added SiO2, but without salt spray corrosion treatment) has the following structure:
[0053] The sensor includes a flexible optical fiber sensing structure, which is composed of a decladding plastic optical fiber core, upconversion nanoparticles (UCNPs), a polydimethylsiloxane (PDMS) matrix, and silica (SiO2) nanofillers. The UCNPs are dispersed in a composite hydrogel precursor composed of PDMS and SiO2 nanofillers, and after thermosetting, they are coated on the surface of the decladding plastic optical fiber core to form a flexible fluorescent optical fiber sensing structure.
[0054] The UCNPs adopt a core-shell structure, consisting of a Gd:Er core layer, a Y:Yb intermediate shell layer, and a Y outermost shell layer from the inside out, and contain Er³⁺ ions with ²H⁺. 11 / 2 energy level and 4 The S3 / 2 level is a pair of thermally coupled energy levels.
[0055] The core material of the plastic optical fiber is polymethyl methacrylate, and the cladding material is fluoropolymer. The bare fiber core is obtained after removing the cladding using a chemical exfoliation method. The mass ratio of the PDMS matrix to the curing agent is 9:1, and the mass fraction of UCNPs in the PDMS precursor is 1.5 wt%. The mass fraction of the SiO2 nanofiller is 3% of the PDMS matrix mass (adjustable between 0.5% and 5%), and spherical nano-SiO2 particles with an average particle size of 20-50 nm are selected.
[0056] The sensor is prepared as follows: First, UCNPs are ultrasonically dispersed in n-hexane to form a dispersion with a concentration of 10 mg / mL; nano-SiO2 particles are ultrasonically dispersed in anhydrous ethanol to form a suspension with a concentration of 5 mg / mL; then, the UCNPs dispersion, SiO2 suspension, PDMS prepolymer, and curing agent are mixed in proportion, stirred evenly, and placed in a vacuum drying oven for degassing for 30 min to obtain a UCNPs-PDMS-SiO2 composite precursor; the decladding plastic optical fiber core is immersed in the precursor and dip-coated at a pulling speed of 2 mm / s, and then placed in an 80°C oven for thermal curing for 2 hours to obtain the sensor.
[0057] The obtained sensor was externally connected to a 980 nm laser excitation source and a spectrometer. The excitation source continuously irradiated the sensor with illumination light, and the spectrometer was used to record the fluorescence spectrum emitted by the sensor. Fluorescence spectra were recorded every 10°C within a temperature range of 40-130°C, based on the ²H of Er³⁺ ions. 11 / 2 energy level and 4 Temperature calibration curves were established using the fluorescence intensity ratio (FIR) of the S3 / 2 level emission peaks (located at approximately 520 nm and approximately 540 nm, respectively).
[0058] Tests showed that, in the initial state without salt spray corrosion treatment, the sensor obtained in this embodiment exhibited improved fluorescence emission intensity compared to Comparative Example 1 due to the enhanced structural stability of the matrix and improved dispersion uniformity of UCNPs resulting from the introduction of SiO2 nanofillers. The light intensity curves at various temperature points were stable, and the FIR value showed an excellent monotonic correlation with temperature. The temperature sensitivity was approximately 0.7% K⁻¹, and the temperature measurement performance was comparable to that of Comparative Example 1.
[0059] Example 2
[0060] A corrosion-resistant flexible fluorescent temperature sensor based on UCNPs-PDMS-SiO2 composite optical fiber (with added SiO2 and subjected to salt spray corrosion treatment) has the same structure as Example 1, except that: after the sensor in this example is prepared, it is further subjected to accelerated aging test in a simulated marine salt spray environment.
[0061] The specific conditions for the salt spray corrosion treatment are as follows: the sensor prepared in Example 1 is placed in a NaCl solution, the test temperature is set at 35°C, the salt spray solution is a 5% NaCl solution, and the continuous immersion time is 48 hours (2 days).
[0062] After salt spray corrosion treatment, the sensor was connected to an external 980 nm laser excitation source and spectrometer, and fluorescence spectroscopy was performed in the temperature range of 40-140°C. A temperature calibration curve was established based on the fluorescence intensity ratio (FIR) of the emission peaks at 520 nm and 540 nm.
[0063] Testing showed that after 48 hours of salt spray corrosion treatment, the fluorescence emission intensity of the sensor obtained in this embodiment was significantly improved compared to Comparative Example 2. This was due to the effective suppression of swelling and microcrack propagation of the PDMS matrix by the SiO2 nanofiller and the protection of the dispersion state of UCNPs. The attenuation of the light intensity curve at each temperature point was significantly reduced, with only about 5%-7% attenuation compared to the initial state of Example 1. The FIR temperature calibration curve maintained good monotonicity and repeatability, and the sensitivity still reached 0.66% K⁻¹, indicating that the sensor with added SiO2 has excellent resistance to salt spray corrosion and long-term stability, making it suitable for in-situ, continuous temperature monitoring under harsh conditions such as offshore dry-type transformers.
[0064] Comparative Example 1
[0065] A corrosion-resistant flexible fluorescent temperature sensor based on UCNPs-PDMS composite optical fiber (without SiO2 addition or salt spray corrosion treatment) has the following structure:
[0066] The sensor includes a flexible optical fiber sensing structure, which is composed of a decladding plastic optical fiber core, upconversion nanoparticles (UCNPs), and a polydimethylsiloxane (PDMS) matrix. The UCNPs are dispersed in a PDMS hydrogel precursor and, after thermosetting, are coated onto the surface of the decladding plastic optical fiber core to form a flexible fluorescent optical fiber sensing structure.
[0067] The UCNPs adopt a core-shell structure, consisting of a Gd:Er core layer, a Y:Yb intermediate shell layer, and a Y outermost shell layer from the inside out, and contain Er³⁺ ions with ²H⁺. 11 / 2 energy level and 4 The S3 / 2 level is a pair of thermally coupled energy levels.
[0068] The core material of the plastic optical fiber is polymethyl methacrylate, and the cladding material is fluoropolymer. The bare fiber core is obtained after the cladding is removed by chemical stripping. The mass ratio of PDMS matrix to curing agent is 9:1, and the doping mass fraction of UCNPs in the PDMS precursor is 1.5 wt%.
[0069] The sensor is prepared as follows: First, UCNPs are ultrasonically dispersed in n-hexane to form a dispersion with a concentration of 10 mg / mL; then, it is mixed with PDMS prepolymer and curing agent in proportion, stirred evenly, and placed in a vacuum drying oven for degassing for 30 min to obtain a UCNPs-PDMS composite precursor; the cladding-removed plastic optical fiber core is immersed in the precursor, and then placed in an 80°C oven for thermal curing for 2 hours to obtain the sensor.
[0070] The obtained sensor was externally connected to a 980 nm laser excitation source and a spectrometer. The excitation source continuously irradiated the sensor with illumination light, and the spectrometer was used to record the fluorescence spectrum emitted by the sensor. Fluorescence spectra were recorded every 10°C within a temperature range of 40-140°C, based on the ²H of Er³⁺ ions. 11 / 2 energy level and 4 Temperature calibration curves were established using the fluorescence intensity ratio (FIR) of the emission peaks of the S3 / 2 energy levels (located at approximately 520 nm and approximately 540 nm, respectively).
[0071] Tests showed that the sensor obtained in this embodiment exhibited a good monotonic correlation between its FIR value and temperature in its initial state without salt spray corrosion treatment, with a temperature sensitivity of approximately 0.78% K⁻¹ and stable fluorescence emission intensity.
[0072] Comparative Example 2
[0073] A corrosion-resistant flexible fluorescent temperature sensor based on UCNPs-PDMS composite optical fiber (without SiO2 added, after salt spray corrosion treatment) has a structure that is basically the same as that of Comparative Example 1. The difference is that after the sensor in this embodiment is prepared, it is further subjected to accelerated aging test in a simulated marine salt spray environment.
[0074] The specific conditions for the salt spray corrosion treatment are as follows: the sensor prepared in Comparative Example 1 is placed in a NaCl solution, the test temperature is set at 35°C, the salt spray solution is a 5% NaCl solution by mass, and the continuous immersion time is 48 hours (2 days).
[0075] After salt spray corrosion treatment, the sensor was connected to an external 980 nm laser excitation source and spectrometer, and fluorescence spectroscopy was performed in the temperature range of 40-130°C. A temperature calibration curve was established based on the fluorescence intensity ratio (FIR) of the emission peaks at 520 nm and 540 nm.
[0076] Testing revealed that after 168 hours of salt spray corrosion treatment, the sensor obtained in this embodiment exhibited slight swelling and microcracks on the PDMS substrate surface, and the UCNP dispersion deteriorated, leading to a significant decrease in fluorescence emission intensity. The light intensity curves at various temperature points showed an average attenuation of approximately 30%-40% compared to Comparative Example 1. The FIR temperature calibration curve remained monotonic, but the temperature measurement accuracy decreased, and the sensitivity dropped to approximately 0.53% K⁻¹, indicating that the sensor without added SiO2 had insufficient corrosion resistance in long-term salt spray environments.
[0077] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A flexible fluorescent temperature sensor, characterized in that, The structure of the flexible fluorescent temperature sensor includes: Plastic optical fiber core, and upconversion cladding layer covering the surface of the plastic optical fiber core; The upconversion coating is formed by thermosetting upconversion nanoparticles, polydimethylsiloxane, silica, and a curing agent.
2. The flexible fluorescent temperature sensor according to claim 1, characterized in that, The mass of the upconversion nanoparticles is 0.5-2 wt% of the mass of the polydimethylsiloxane.
3. The flexible fluorescent temperature sensor according to claim 1, characterized in that, The mass of the silica is 0.5-5 wt% of the mass of the polydimethylsiloxane.
4. The flexible fluorescent temperature sensor according to claim 3, characterized in that, The average particle size of the silica is 20-50 nm.
5. The flexible fluorescent temperature sensor according to claim 1, characterized in that, The upconversion nanoparticles have a three-layer core-shell structure, consisting of a Gd:Er core layer, a Y:Yb intermediate shell layer, and a Y outermost shell layer from the inside out.
6. The flexible fluorescent temperature sensor according to claim 1, characterized in that, The mass ratio of polydimethylsiloxane to curing agent is (8-10):
1.
7. The flexible fluorescent temperature sensor according to claim 1, characterized in that, The plastic optical fiber core material is selected from at least one of polymethyl methacrylate, polycarbonate, cyclic olefin copolymer, and fluoroplastics.
8. A method for fabricating a flexible fluorescent temperature sensor according to any one of claims 1-7, characterized in that, Includes the following steps: Upconversion nanoparticles, silica, polydimethylsiloxane, and curing agent were mixed in proportion, stirred, and degassed to obtain a UCNPs-PDMS-SiO2 composite precursor. The cladding-removed plastic optical fiber core was immersed in the UCNPs-PDMS-SiO2 composite precursor for impregnation, pull coating, and then thermal curing to obtain the flexible fluorescent temperature sensor.
9. The method for fabricating the flexible fluorescent temperature sensor according to claim 8, characterized in that, The thermosetting temperature is 70-90°C, and the time is 1.5-3 hours.
10. The application of the flexible fluorescent temperature sensor according to any one of claims 1-7 in temperature monitoring of offshore dry transformers.